Origin of samples of Cannabis sativa through insect fragments associated with compacted hemp drug in South America - Macedo, Marcos Patrício (2013)
Origin of samples of Cannabis sativa through insect fragments associated with compacted hemp drug in South America. Insects associated with a seizure of Cannabis sativa L. may indicate the origin of the illicit drug. Nevertheless, no work regarding this subject has been previously published for South America. In the present investigation, seven kilograms of vegetal material (C. sativa) were inspected for insect fragments. Three species were identified and used to test the origin of the seizure of cannabis plant material: Euschistus heros (Fabricius, 1794), Thyanta perditor (Fabricius, 1794) (Heteroptera, Pentatomidae), and Cephalotes pusillus (Klug, 1824) (Hymenoptera, Formicidae). These insect species restricted the geographic origin of the drug to the Neotropical region, and their distribution patterns showed an overlap of the State of Mato Grosso (Brazil), Argentina, and Paraguay. Based on this information, two of the three major C. sativa growing areas in South America were excluded: (1) the Colombian territory and (2) northeastern Brazil.